Histochemical aspects of reserves mobilization of Caesalpinia peltophoroides (Leguminosae) seeds during germination and seedlings early growth - Corte, Viviana Borges; Borges, Eduardo Euclydes de Lima e; Ventrella, Marília Contin; Leite, Idalina Tereza de Almeida; Braga, Antônio Jorge Tourinho (Revista Árvore, 2008)
The objective of this study was to investigate reserve mobilization in Caesalpinia peltophoroides seeds during germination and initial seedling growth. The variation in these compounds was analyzed from the pre-germination period (0 to 5 days after sowing - DAS) to the total cotyledon senescence and abscission at 35 DAS. For this histochemical tests were made on cotyledons fixed in FAA50 or included in glycol-metacrylate. To follow the mobilization of the main reserve compounds, sudan III was used to detect total lipids, xylidine Ponceau to detect total proteins, lugol to detect starch and polarized light to visualize the crystals. The lipids, present in a great quantity in the cotyledon, gradually decreased in the period studied. A greater quantity of starch was observed on the 10th DAS than in the previous periods and it was totally consumed by 30 DAS. The distribution pattern and the morphology of the protein material were very modified by 10 DAS, a period during which it was intensely consumed, remaining only parietally fragments distributed, that practically disappeared at 25 DAS. The calcium oxalate druses were not consumed during the period studied, there was only crystal agglutination.

Este trabalho teve como objetivo o estudo da mobilização de reservas de sementes de Caesalpinia peltophoroides Benth. durante a germinação e crescimento inicial das plântulas. As variações nesses compostos foram analisadas desde o período pré-germinativo (0 a 5 dias após a semeadura - DAS) até a total senescência e abscisão dos cotilédones, aos 35 DAS. Para isso, foram realizados testes histoquímicos em cotilédones fixados em FAA50 ou incluídos em glicol-metacrilato. Para acompanhamento da mobilização dos principais compostos de reserva, foi usado o sudan III para detecção de lipídios totais, xylidine Ponceau para proteínas totais, Lugol para amido e luz polarizada para visualização dos cristais. Os lipídios, presentes em maior quantidade nos cotilédones, apresentam decréscimo gradativo no período estudado. No 10º DAS, observou-se maior quantidade de amido que nos períodos anteriores, sendo totalmente consumido até os 30 DAS. O padrão de distribuição e morfologia do material protéico modificaram-se bastante até os 10 DAS, período em que foi intensamente consumido, restando apenas fragmentos parietalmente distribuídos, que praticamente desaparecem após 25 DAS. As drusas de oxalato de cálcio não foram consumidas durante o período estudado, apenas houve aglutinação dos cristais.
Keywords: Reserve materials; Carbohydrates; Lipids; Proteins and calcium oxalate